Establishing molecular microbiology facilities in developing countries. Issue 6 (November 2015) - Ahmed, Salman S.; Alp, Emine; Ulu-Kilic, Aysegul; Doganay, Mehmet
Summary Microbiology laboratories play an important role in epidemiology and infection control programs. Within microbiology laboratories, molecular microbiology techniques have revolutionized the identification and surveillance of infectious diseases. The combination of excellent sensitivity, specificity, low contamination levels and speed has made molecular techniques appealing methods for the diagnosis of many infectious diseases. In a well-equipped microbiology laboratory, the facility designated for molecular techniques remains indiscrete. However, in most developing countries, poor infrastructure and laboratory mismanagement have precipitated hazardous consequences. The establishment of a molecular microbiology facility within a microbiology laboratory remains fragmented. A high-quality laboratory should include both conventional microbiology methods and molecular microbiology techniques for exceptional performance. Furthermore, it should include appropriate laboratory administration, a well-designed facility, laboratory procedure standardization, a waste management system, a code of practice, equipment installation and laboratory personnel training. This manuscript lays out fundamental issues that need to be addressed when establishing a molecular microbiology facility in developing countries.